Hot and Cool Executive Functions in Adolescence: Development and Contributions to Important Developmental Outcomes - Poon, Kean (Frontiers in Psychology, 2018)
Despite significant theoretical advancement in the area of child neuropsychology, limited attention has been paid to the developmental features of adolescence. The present study intends to address this issue in relation to executive function (EF). EF refers to the psychological processes that underlie goal-directed behavior; recent studies separate cool EF (psychological process involves pure logic and critical analysis) and hot EF (psychological process driven by emotion). Although neurological findings suggest that adolescence is a sensitive period for EF development, data on comparing the developmental progression in hot or cool EFs is highly missing. Moreover, while evidence has confirmed the relationships between EF and day-to-day functioning, whether and how hot and cool EFs contribute to core developmental outcomes in adolescence is still remained unknown. The current study aims to enhance our understanding of the development and impacts of hot and cool EFs in adolescence. A total of 136 typically developing adolescents from age 12 to 17 completed four cool EF tasks including Backward digit span, Contingency naming test, Stockings of Cambridge and Stroop Color and Word test, and one hot task on Cambridge gambling task. Data on academic performance and psychological adjustment was also collected. Results showed that cool and hot EF exhibited different patterns of age-related growth in adolescence. Specifically, cool EF ascended with age while hot EF showed a bell-shaped development. Moreover, there were significant correlations among cool EF measures but no association between cool and hot EFs. Further, cool EF was a better predictor of academic performance, while hot EF uniquely related to emotional problems. The results provide evidence for the association among cool EF tests and the differentiation of hot and cool EFs. The bell-shaped development of hot EF might suggest a period of heightened risk-taking propensity in middle adolescence. Given the plastic nature of EF, especially over adolescence, the current findings may have practical implications for future EF identification and training.